Needs Analysis of Interactive Infographic Media Development with Vehicle-Themed Project Based Learning Model for Kindergarten B Children - Herlambang, Yoanita Andofjul; Raharjo, Makmum; Safitri, Erna Retna (Journal of Educational Sciences, 2025)
Early Childhood Education (ECED) plays a vital role in shaping children's cognitive, social, and motor development. However, implementing innovative learning methods remains a significant challenge. This study analyzes the need for developing interactive infographic media based on the Project-Based Learning (PjBL) model on the theme of vehicles for kindergarten B children. The research responds to children's low understanding of the theme, using a quantitative descriptive method with data collected via Guttman scale questionnaires involving 10 students and 2 teachers at Adventure Islamic Kindergarten Palembang. Findings show that the children’s understanding level of the vehicle theme averaged 1.3, indicating a high need for more engaging and communicative media. Teachers also indicated a high level of need, with an average score of 1.5, emphasizing the importance of media aligned with the PjBL approach. The results conclude that developing interactive infographic media has strong potential to enhance children’s conceptual understanding, boost learning motivation, and encourage active participation in thematic project-based learning in a fun and effective manner.